Pulmonary hypertension in heart failure. (March 2021) - Duran, Antonio; Mandras, Stacy
Abstract : Purpose of review: Pulmonary hypertension (PH) occurs frequently in heart failure (HF) and confers worse prognosis. It becomes important to adequately identify these patients to optimize treatment. The purpose of this review is to inform about the updated classification of PH in left heart disease, in addition to current and upcoming trials regarding treatment. Recent findings: The updated classification of PH due to left heart disease now utilizes pulmonary vascular resistance instead of diastolic pulmonary gradient to differentiate between isolated postcapillary and combined pre and postcapillary PH. In regards to treatment, recent clinical trials continue to provide data that pulmonary vasodilators do not improve outcomes in this population. Summary: Management of underlying heart disease and optimal control of comorbidities continues to be the mainstay of treatment in PH due to HF. At this time, current data does not support the use of PH-directed therapies.